logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  EAMCET  >>  Mathematics
0 votes

The solution of the differential equation $xy^2 dy-(x^3+y^3)dx=0$ is

\[\begin {array} {1 1} (1)\;y^3=3x^3+C & \quad (2)\;y^3=3x^3 \log (Cx) \\ (3)\;y^3=3x^3+ \log (Cx) & \quad (4)\;y^3+3x^3= \log (Cx) \end {array}\]
Can you answer this question?
 
 

1 Answer

0 votes
$(2)\;y^3=3x^3 \log (Cx)$
answered Nov 7, 2013 by pady_1
 
Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...